Coping and personality in the adaptation of younger in their sport practice. Gender differences - González, J.; Martínez Sandoval, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The purpose of this cross-sectional study is finding coping strategy signs in a young people sample, differentiating on gender, age, and regular physical activity. The sample is composed by young people (N=119) aged between 11 and 19, administering questionaires of personality measure (NEO-FFI) and coping (CSI). The results show that boys have a higher average in appropriate and inappropriate coping strategies. Also, they scored higher in self-criticism, social support, cognitive restructuring, problem avoidance and social withdrawal, while girls scored higher in problem solving, wishful thinking and emotional expression.